Preserving and exhibiting media art : challenges and perspectives - Noordegraaf, Julia; Saba, Cosetta G.; Le Maître, Barbara; Hediger, Vinzenz, 1969- (Framing film., 2013)
Artists have always experimented with the potentials film, video and digital technology. 'Preserving and Exhibiting Media Art' highlights the challenges these new multimedia works pose to the traditional ways of collecting, preserving and exhibiting art. In addition, it outlines several case studies through the contours of the training and education of professionals in this field. The book offers a historical and theoretical overview and makes an important contribution to the literature on archival theory and practice and is a reference point for anyone concerned with the preservation and presentation of media art.